Stable solid electrolyte interphase induced by Ag@graphite dual-functional layer in lithium metal anode - Nanbiao Pei; Jiaxiang Liu; Yaqi Zhang; Xueying Yang; Yi Deng; Peng Zhang; Jinbao Zhao (Next Materials)
The thermodynamically unstable solid electrolyte interphase (SEI) film and infinite volume expansion during the plating/stripping of lithium metal anode (LMA) are important reasons for inhibiting the cycle lifespan of lithium metal batteries (LMBs). It is of great significance to introduce a SEI similar to lithium-ion batteries (LIBs) on the LMA to improve the lifespan of LMBs. In this work, the graphite was cleverly covered on the LMA to induce the formation of a uniform and stable SEI, protect Li metal and obtain a stable anode interface. Moreover, a thin silver (Ag) layer with excellent lithiophilic and conductivity was introduced before covering graphite to improve the migration kinetics of Li+ ions in the graphite layer. Under the synergistic effect of them, a stable SEI was successfully induced and the volume change of LMA was reduced. As a result, LMBs modified by Ag-Graphite layer (Ag-Graphite@Li) have showed better electrochemical properties. And Ag-Graphite@Li anode//NCM523 cell could maintain a capacity retention of 78.3 % for 400 cycles at 0.5 C in carbonate-based electrolytes. This work provides an effective strategy for improving the cycle lifespan of LMBs.